Parametric investigation of effectiveness of high modulus columns in liquefaction mitigation - Demir, Selcuk; Ozener, Pelin Tohumcu (ELSEVIER SCI LTD, 2020)
In this paper, an extensive parametric study is carried out in order to examine the effectiveness of high modulus columns (HMCs) in liquefaction mitigation using a nonlinear three-dimensional (3D) finite-element (FE) software. For this purpose, a hypothetical liquefiable soil profile of 20 m thick is modeled and parametric analyses are performed by considering different area replacement ratios, shear modulus ratios, improvement depth (slenderness) ratios and input motion intensities. The results of the parametric analyses are evaluated by examining shear stress reduction, shear strain distribution, peak surface acceleration, maximum horizontal acceleration, factor of safety against soil liquefaction, excess pore water pressure ratio, surface settlements, lateral displacements and response spectra. Comparative analyses between unimproved liquefiable soil and improved soil are performed to show the influence of high modulus columns on the response of liquefiable soil. The seismic performance of liquefiable soil reinforced with HMCs is specifically investigated by focusing on the shear strain and shear stress distribution between liquefiable soil and high modulus columns. Therefore, the analysis results are discussed in terms of assumption of shear strain compatibility by comparing the modified equations for shear stress reduction factors suggested in the literature with the one developed in this paper. Additionally, the reliability of the current design methodology for evaluating shear reinforcement of HMCs is discussed by showing effects of shear strain compatibility and incompatibility on the values of factor of safety against liquefaction and recommendations are made related to the use of HMCs in engineering practice.
Keywords: Liquefaction mitigation; Shear strain compatibility; High modulus columns; Numerical modeling; OpenSeesPL; NUMERICAL-SIMULATION; LIQUEFIABLE SOIL; STONE COLUMNS; MODEL; PERMEABILITY; PERFORMANCE; BEHAVIOR; DRAINS; Engineering; Geology